Dependence of light-saturated photosynthesis on temperature and community structure - Bouman, H; Platt, T; Sathyendranath, S; Stuart, V (2005)
Using data collected in the Arabian Sea and on the Nova Scotian Shelf we examined the relationships between temperature, phytoplankton taxonomic composition (indexed by pigment composition) and the size structure (indexed by chlorophyll-specific absorption coefficient at 676 nm), Chlorophyll-a biomass and the light-saturated photosynthesis parameter PmB. Our results show that changes in phytoplankton community structure for the Scotian Shelf closely follow changes in temperature. In the Arabian Sea the relationship between phytoplankton community structure and temperature was less striking and fluctuations in phytoplankton pigment composition were strongly related to Chlorophyll-a biomass. The light-saturated photosynthesis parameter P mB was correlated with temperature for the Scotian Shelf. When we compared data collected on the Scotian Shelf with the temperature-dependent function of Eppley (1972. Fishery Bulletin 70, 1063-1085), the model fitted the data remarkably well. For the Arabian Sea data, however, only a weak temperature dependence in PmB was observed, which may be a result of a strong negative correlation between ambient nitrate concentration and temperature. Our results also show that for both the Scotian Shelf and the Arabian Sea, diatom-dominated waters had similarly low P mB values even though the temperatures of the two systems were markedly different. The absorptive characteristics of phytoplankton on the Scotian Shelf were well correlated with PmB, thus providing another potential predictor of PmB that may, in the future, be routinely accessible by remote sensing. The contrasting relationships among community structure, temperature, and primary production observed in the two study regions suggest that primary production algorithms incorporating such information could be developed and applied on a domain-specific basis. These algorithms should be centred on knowledge of the relationships between physical forcing, community structure and phytoplankton photophysiology. © 2005 Elsevier Ltd. All rights reserved.